Patient-Reported Burden of Illness in a Prevalent COPD Population Treated with Long-Acting Muscarinic Antagonist Monotherapy: A Claims-Linked Patient Survey Study - Beth Hahn; Richard H. Stanford; Alyssa Goolsby Hunter; Breanna Essoi; John White; Riju Ray (Pulmonary Therapy, 2019)
Abstract Introduction Symptom burden in inadequately controlled chronic obstructive pulmonary disease (COPD) considerably impacts quality of life, healthcare resource utilization (HCRU) and associated costs. This claims-linked cross-sectional survey study assessed symptom burden and HCRU among a prevalent population of COPD patients prescribed long-acting muscarinic antagonist (LAMA) monotherapy. Methods Patients were identified using claims data from the Optum Research Database. Eligible patients were aged ≥ 40 years with 12 months’ continuous enrollment in a US health plan, ≥ 2 medical claims containing COPD diagnosis codes ≥ 30 days apart, and ≥ 2 claims for LAMA monotherapy in the latter half of the 12-month sample identification period. Patients were mailed a cross-sectional survey assessing patient-reported outcomes (PROs) [COPD assessment test (CAT) and modified medical research council dyspnea scale (mMRC)], clinical characteristics, smoking history, and demographics. Patients also completed the Exacerbations of Chronic Pulmonary Disease Tool (EXACT-PRO) daily diary for 7 days. HCRU was assessed from claims data. Results The study included 433 patients with a self-reported healthcare provider COPD diagnosis, and both claims-based and self-reported LAMA monotherapy treatment (mean age 71.0 years; 59.8% female). Most patients (85.5%) reported a high symptom burden (CAT score ≥ 10), 45.5% had high levels of dyspnea (mMRC grade ≥ 2), and 64.4% reported more severe daily symptoms by the EXACT-PRO. Most patients (71.6%) reported high scores on ≥ 2 PROs. More patients with high symptom burden had COPD-related emergency department visits than those with lower disease burden (27.6% vs 12.7%, P = 0.012). Conclusions In conclusion, a large proportion of patients with COPD receiving LAMA monotherapy experienced a high symptom burden and may benefit from therapy escalation. Healthcare professionals can use validated PROs to help them assess symptom burden. Funding GlaxoSmithKline (GSK study number: 205862)